A rare case of congenital insensitivity to pain with anhydrosiss - Govardhani Yanamadala; Varaprasad Ussa; Pavani Medisetty; Bhavya Gatte (Indian Journal of Pain, 2015)
Congenital insensitivity to pain syndrome with anhydrosis (CIPA) is a rare inherited disorder. It is characterized by loss of pain and temperature sensation, lack of sweating and mild mental retardation. This disorder belongs to hereditary sensory and autonomic neuropathy family (type IV). Because of these abnormalities, patients require special anesthetic care. They include titration of intraoperative opioids, an anesthetic to ensure co-operation and immobility and intra-operative temperature monitoring. Here we report a 7-year-old female child with CIPA posted for restoration and cementation for dental caries along with sural nerve and skin biopsy.